The effect of reducing the incidence of gastrointestinal complications in patients treated with aspirin, referred to Imam Hospital, of Ahvaz, Iran - Abdalrahim Masjedizade (Data in Brief, 2017)
This research contains data which were obtained during the analysis of treated patients with aspirin who were referred to Imam Hospital (Imam H) of Ahvaz, Iran; and the effect of this type of treatment (Helicobacter pylori eradicate (HPE)) on reducing the incidence of gastrointestinal complications. Studies have shown that taking aspirin in patients with Helicobacter pylori infection is associated with a decreasing risk of gastrointestinal bleeding (O'connor et al., 2013) [1]. In this study, 165 patients with positive helicobacter pylori infection test were chosen among those who were referred to Imam H. In this paper, the effects of sex, smoking, renal failer, diabetes, age, blood pressure and aspirin consumption have been studied (Fletcher et al., 2010) [2]. After completion of the observations and records of patient's medical records, the obtained coded data were fed into EXCELL. Data analysis was performed, using SPSS 16. Keywords: Helicobacter pylori, Aspirin, Patients, Imam Hospital, Iran